2017
DOI: 10.20471/acc.2017.56.03.19
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Osteodystrophy: A Global (Re)View of the Problem

Abstract: Hepatic osteodystrophy is a common and frequently untreated complication, manifested as osteoporosis or osteopenia, encountered in the evolution of chronic liver diseases. This article provides a narrative review of hepatic osteodystrophy. The aim is to revise the prevalence, pathophysiology, diagnosis and management of hepatic osteodystrophy. We searched medical literature via PubMed, Google Scholar, Wiley, Science Direct, and Springer Link using respective keywords to obtain data on low bone mineral density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In addition, in SCD patients we observed a significant correlation between abnormal AST and vertebral fracture, suggesting a possible role of sickle cell related hepatopathy in SBD. Previous studies in other models of hepatic osteodystrophy demonstrated the relationship between hepatic function and bone metabolism, vitamin D levels and bone density [43][44][45]. Inflammatory vasculopathy and chronic hemolysis play a key role in both acute and chronic sickle cell related organ complication [2].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, in SCD patients we observed a significant correlation between abnormal AST and vertebral fracture, suggesting a possible role of sickle cell related hepatopathy in SBD. Previous studies in other models of hepatic osteodystrophy demonstrated the relationship between hepatic function and bone metabolism, vitamin D levels and bone density [43][44][45]. Inflammatory vasculopathy and chronic hemolysis play a key role in both acute and chronic sickle cell related organ complication [2].…”
Section: Discussionmentioning
confidence: 98%
“…HO is an osteometabolic disease that presents with low BMD and changes in bone microarchitecture, and it constitutes a reasonable experimental model for evaluating osteoporosis (46). In this model, hepatic impairment leads to metabolic disturbances that causes loss of bone mass (37,38,46,47), however the pathogenesis is not fully A B understood (48). Some studies have shown that decreased bone formation is the predominant mechanism (47), while others point to increased bone resorption as the main cause of bone loss (49).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple risk factors for hepatic osteodystrophy in liver disease including genetic factors, vitamin D deficiency and calcium disorders, vitamin K deficiency, IGF-1 deficiency, hyperbilirubinemia, hypogonadism, medication, fibronectin, hyperhomocysteinemia, leptin and lifestyle. 46 Osteoprogenitor cells are reduced in patients with cirrhosis. 47…”
Section: Pathogenesis Of Sarcopenia In Cirrhosismentioning
confidence: 99%